(untitled) (Journal of Medicine, 2025)
A bronchobiliary fistula or a biliobronchial fistula is a uncommon condition which occurs from an abnormal connection between the bronchial trees and biliary channel.It presents with pathognomonic bilious sputum or biloptysis with suspicious pneumonia.Broncho-biliary fistula is associated with Hydatid infection but recently found in patients with tumours.This case report presents a patient who had bronchobiliary fistula who had history of Adenocarcinoma of gall bladder with multiple space occupying lesions in liver and she underwent cholecystectomy. J MEDICINE 2025; 26: 71-73